THE INDIVIDUALITY SPHERES OF HEALTH PROFESSIONALS - Nesyna, Svetlana; Nesyn, Vladislav (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2018)
This study focuses on the health professionals’ spheres of individuality. We surveyed three groups of health professionals – anaesthesiologists, cardiac surgeons, and cardiologists. The respondents were asked to complete an individuality questionnaire for health professionals – an update of T. Grebenuk’s questionnaire for measuring teachers’ individuality. The survey results show that a medical specialist’s individuality is an integrated system comprising seven interconnected spheres – intellectual, motivational, volitional, emotional, practical and object-oriented, existential, and self-regulative ones, – which are affected by the development of professionally relevant components. The dominant sphere is motivational. Age and experience are associated with a lower rating given to all the components – chiefly, motivational, volitional, and self-regulative ones. No significant difference was observed between the male and the female respondents. However, the spheres of individuality differed across the three groups of health professionals. The anaesthesiologists were inclcned to give average ratings. The surgeons’ and cardiologists’ spheres of individuality showed significant similarities.